Influence of regular exercise training on post-exercise hemodynamic regulation to orthostatic challenge - Sugawara, Jun; Komine, Hidehiko; Miyazawa, Taiki; Imai, Tomoko; Ogoh, Shigehiko (Frontiers in Physiology, 2014)
To prevent orthostatic hypotension, arterial blood pressure (BP) is neurally and hormonally regulated via increases in heart rate (HR) and peripheral vascular tone. After dynamic exercise, however, the latter arm is blunted because of the increased vasodilators in exercised muscles. Orthostatic tachycardia is likely a more important compensatory mechanism for post-exercise orthostatic intolerance in individuals who have higher leg vasodilator capacity, such as endurance-trained athletes. To test the hypothesis that regular endurance training was associated with the greater augmentation of tachycardia response to post-exercise orthostasis, we compared hemodynamic responses to 5-min 60-degree head-up tilt (HUT) before and after 60 min of cycling at 70% of HR reserve in the endurance-trained (n=8) and sedentary men (n=9). Calf peak vascular conductance was 62% greater in the endurance-trained than the sedentary (P<0.001). After the exercise, the HUT-induced reduction of SV was significantly augmented in the endurance-trained (from -27.7±6.9 to -33.7±7.7 ml, P=0.03) but not in their sedentary peers. Nevertheless, MAP was well maintained during post-exercise HUT even in the endurance-trained (from 81±10 to 80±8 mmHg). Tachycardia responses during sustained orthostasis were significantly increased in the sedentary (1.3-fold vs. pre-exercise) and more in the endurance-trained (2.0-fold). The augmented response of HUT-induced tachycardia was greater in the endurance-trained than the sedentary (P=0.04). Additionally, cardiovagal baroreflex sensitivity (BRS), evaluated by the HR response to the hypotensive perturbation, was improved after the exercise in the endurance-trained (from -0.56±0.32 to -1.03±0.26 bpm/mmHg, P=0.007) but not in the sedentary. These results suggest that in the endurance-trained men the increased orthostatic tachycardia and augmented cardiovagal BRS may favorably mitigate accumulated risks for orthostatic intolerance in the early phase of post-exercise.